2012
DOI: 10.1007/978-3-642-33093-3_5
|View full text |Cite
|
Sign up to set email alerts
|

Gaze Allocation Analysis for a Visually Guided Manipulation Task

Abstract: Findings from eye movement research in humans have demonstrated that the task determines where to look. One hypothesis is that the purpose of looking is to reduce uncertainty about properties relevant to the task. Following this hypothesis, we define a model that poses the problem of where to look as one of maximising task performance by reducing task relevant uncertainty. We implement and test our model on a simulated humanoid robot which has to move objects from a table into containers. Our model outperforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It is important to evaluate how much these differences affect task performance. We have already demonstrated that the RUG gaze strategy outperforms two common baselines: random and round robin schemes [Nunez-Varela et al 2012b]; we have also characterised this model's robustness in terms of variations of three environmental variables [Nunez-Varela et al 2012a]. In this article, our new results show how the RUG model is the most effective of the three strategies presented earlier, along with the baselines.…”
Section: Gaze Control Based On Rewards Uncertainty and Gain (Rug)mentioning
confidence: 67%
See 2 more Smart Citations
“…It is important to evaluate how much these differences affect task performance. We have already demonstrated that the RUG gaze strategy outperforms two common baselines: random and round robin schemes [Nunez-Varela et al 2012b]; we have also characterised this model's robustness in terms of variations of three environmental variables [Nunez-Varela et al 2012a]. In this article, our new results show how the RUG model is the most effective of the three strategies presented earlier, along with the baselines.…”
Section: Gaze Control Based On Rewards Uncertainty and Gain (Rug)mentioning
confidence: 67%
“…This analysis makes use of the pick & place task (Section 1.2), which consists of picking up objects from the tabletop and then placing them inside one of two containers. Even though the aim is to make comparisons between our three gaze control models, two more gaze schemes are presented that serve as a common baseline and provide a more general analysis [Nunez-Varela et al 2012a]:…”
Section: Experimental Analysis For the Pick And Place Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…Shahzad and Mehmood (2010) presented a master’s thesis on controlling articulated robot arms using eye tracking. ( Nunez-Varela, 2012 ), focusing on task-driven object manipulation by gaze locations on the object (intention read from gaze). The MyEccPupil (HomeBrace GmbH) is a commercially available eye tracking controller for a wheelchair-mounted robotic arm.…”
Section: Resultsmentioning
confidence: 99%
“…The approach we take here is to consider vision as part of a control process where a human, or agent, actively chooses taskrelevant information from the environment to guide actions and achieve goals [4][5][6][7][8]. Our visual task module approach is inspired by human visual behaviour, in particular a foveated visual system that can be highly specific in accessing particular pieces of information over time.…”
Section: Modelling Visual Attentionmentioning
confidence: 99%